Exposure to workplace bullying and wellbeing among Ghanaian nurses: The role of personal resources - Justice Mensah; Kwesi Amponsah-Tawiah; Nana Kojo Ayimadu Baafi (Elsevier, 2024)
The present study examined the effect of workplace bullying on employee wellbeing, and the moderating effects of psychological capital and emotional intelligence in the workplace bullying and employee wellbeing relationship. Data was collected from 224 nurses in a teaching hospital in Ghana. The results of the analysis showed that workplace bullying has a negative effect on the psychological wellbeing of employees. Furthermore, the results showed that psychological capital and emotional intelligence moderated workplace bullying and psychological wellbeing relationship. The present study makes some contributions to theory and practice. Theoretically, the study extends the literature on the JD-R by highlighting the significant effect of personal resources in mitigating the effects of workplace bullying on employee wellbeing.